Strategi Membangun Bisnis UMKM “Sate Bebek Hj. Siti” Kuliner Khas Cilegon - Siti Hailatul Fikriyah; Moh Yuddy Yudawirawan; Nelly Budiyarti; Sutandijo Sutandijo; Dewi Rani Gustiasari (Abdimisi, 2021)
The Covid-19 pandemic is still not over, many employees are finally laid off due to an unstable economy. This of course makes some people have to think hard to survive, especially with difficult economic conditions. One of them is to open your own business or entrepreneurship. This Community Service was carried out at the Al – Kamilah Foundation, Depok, West Java. The purpose of holding this PKM is to share insights about the culinary business with the students at the foundation. The PKM method used is to provide presentation materials on how to start a culinary business, marketing techniques, to financial management procedures. The results obtained by the existence of this PKM are to increase the knowledge of students about the culinary business, especially the culinary area of Cilegon which is not yet known by many people. After participating in this PKM, the students became enthusiastic about becoming culinary entrepreneurs.